Relationship Between Systemic Lupus Activity Measurement (SLAM) Score and Mortality in Systemic Lupus Erytemathosus (SLE) Inpatients - Paramaiswari, Ayu; Kertia, Nyoman; Achadiyono, Deddy Wachid (Acta Interna The JOurnal of Internal Medicine, 2014)
ABSTRACTBackground: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disorder that can be severeand life threatening. Mortality in SLE may due to lupus activity or long-term sequel. Systemic Lupus ActivityMeasurement (SLAM) score is a tool that can count lupus disease activity inpatients.Aims: To analyze the relationship between SLAM score and mortality in lupus inpatients.Methods: Retrospective cohort study used for reaching objective of the study. Lupus inpatients was usedas research population. Medical record was used as study data collection over periods of 2006 until 2011.Independent variable was a SLAM score. The cut point of SLAM score was made based on the mean ofSLAM score (16.7 point score). Dependent variable was mortality.Results: There were differences between number of ACR criteria fi ndings, pneumonia, heart rate withSLAM score (p value 0.001; 0.001; 0.002 respectively).There was a difference of median survival between less and more than 16.7 point score, 45 and 28 respectively (p 0.034). There was a relationship betweenSLAM score (more than 16.7 point score) and mortality HR 2.78 (96% CI 1.01-7.53).There was a differenceof mortality incidence between more and less than 16.7 point score, 0.35 and 0.10 respectively. There wasa relationship between SLAM score (more than 16.7 point score) and mortality RR 3.5 (95% CI). Mortalityin lupus inpatients was 23%.Conclusion: There was a relationship between SLAM score and mortality on lupus inpatients.Keywords: SLE, SLAM, Mortality